Interleukin-10 gene polymorphism in patients with systemic lupus erythematosus and normal individuals of Kasakh population - Z E Omarbekova; R L Ivanova; I A Guseva; V A Myakotkin (Научно-практическая ревматология, 2003)
An analysis of interleukin-10 (IL-10) gene polymorphism associative link with clinical variability in Kasakhs. 49 pts with systemic lupus erythematosus were included (48 female and I male). Promotive IL-10 gene region determined by a point variable in 627 locus was assessed with restrict fragment length polymorphism method using restrictase Rsal. The results showed allele IL-10 gene polymorphism significance in disease risk determination, clinical variability and features of pathological process course in Kasakhs.